42 Life stories by Qulutanguaq Jeremiassen (part 5) - Leonard, Stephen Pax (2011)
This is the fifth in a series of recordings, documenting the life of Qulutanguaq Jeremiassen. Qulutanguaq is the oldest member of the community (88 years old) and is considered the best living story-teller in the region. Qulutanguaq continues to talk about his travels in north-west Greenland and his life as a hunter .wav and .mp3 audio file